Wire Injury-Induced Moderate Aortic Valve Stenosis in Mice Is Accompanied by a Chronic Systemic Inflammatory Reaction - Katrin Becker (Cells)
Background/Objectives: While the presence of inflammatory processes in stenotic aortic valves is acknowledged, no systematic characterization of the systemic immune reaction upon aortic valve stenosis (AS) has been performed yet. The hypothesis of this study was that AS induces a systemic inflammatory reaction linked with local processes in the heart. Methods: Murine wire injury (WI) to induce AS, or sham surgery, were performed prior to the 4-week assessment of AS severity, left ventricular (LV) function and hypertrophy with echocardiography (echo). Organ weights, levels of leukocytes, cytokines and costimulatory molecules in blood, heart, and peripheral immune organs (spleen, liver, lymph nodes), and immune cell uptake of Cy5-labelled perfluorocarbon nanoemulsions were measured. Results: Trends towards correlation were found between organ weights, myocardial immune cells and echo. Cytokine mRNA levels trended mainly towards an increase in heart and regional lymph nodes and a reduction in spleen and liver, and correlation with echo was more homogeneous after WI. Unchanged cytokine protein levels in myocardium and plasma trended to correlate with echo. A homogeneous pattern was found for echo and costimulatory molecule correlation, while PFC uptake by lymphatic cells was reduced upon AS. Conclusions: The results suggest a link between number and activation state of leukocytes in peripheral organs and cardiac processes in AS. Considering the pathological value of inflammation, it is crucial that future studies investigate if a modulation of the systemic inflammatory reaction relieves severity of AS and opposes development of heart failure.